Amandemen Undang-Undang Dasar 1945: Upaya Penegakan HAM di Indonesia - Aina, Aina (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2002)
Many Indonesian perceive that UUD 1945 as Indonesian constitution is sacred. This sence is widely believed until the end of New Order regime. Up to now, the constitution has been amended for two times, that is amendment 1 and amendment 2. These two amendments are believed as an entry point headed for further steps of democratization after the fall of Soehartoâ€™s regime and is an effort for the establishing of Human Rights in Indonesia.Â Key Words: Amandemen, UUD 1945, Hak Asasi Manusia